2007
DOI: 10.5650/jos.56.569
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effect of .GAMMA.-Linolenic Acid on the Lipid Profile of Rat Fed Erucic Acid Rich Oil

Abstract: This study evaluated the effects of dietary supplementation of g-Linolenic acid (18:3n-6, GLA) on the lipid profile of serum and other tissues of rats fed erucic acid (C22:1) rich oil like mustard oil. The rats were fed diet containing 20% mustard oil as erucic acid rich oil and 20% groundnut oil as dietary fat. These groups were kept as reference groups. Another group fed diet containing 20% fat to which evening primrose oil as a source of GLA was blended with mustard oil and groundnut oil at 5% level. The fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…This results have similarities with previous studied [29,30]. Many reporters have been reported that feeding high levels of rapeseed oil to rats significantly increased cholesterol levels in the adrenal glands and lipidosis in the cardiac tissue and also found that erucic acid may cause some adverse effect in lipid profile of serum [31]. Additionally when rats were fed to diet in combination with coconut oil and sesame oil exhibited significant depletion of serum cholesterol level as compared to mustard oil and slightly increased than control group result showed in Table 3.…”
Section: Fig 1 the Average Weight Body Gain Of The Rats Was Measuresupporting
confidence: 91%
See 1 more Smart Citation
“…This results have similarities with previous studied [29,30]. Many reporters have been reported that feeding high levels of rapeseed oil to rats significantly increased cholesterol levels in the adrenal glands and lipidosis in the cardiac tissue and also found that erucic acid may cause some adverse effect in lipid profile of serum [31]. Additionally when rats were fed to diet in combination with coconut oil and sesame oil exhibited significant depletion of serum cholesterol level as compared to mustard oil and slightly increased than control group result showed in Table 3.…”
Section: Fig 1 the Average Weight Body Gain Of The Rats Was Measuresupporting
confidence: 91%
“…The erucic acid containing mustard oil might be causative factor for increasing LDL. Other researcher also showed this same phenomena [31]. In this study, it was found that sesame oil was decreased LDL than mustard oil group.…”
Section: Fig 1 the Average Weight Body Gain Of The Rats Was Measuresupporting
confidence: 68%
“…Gamma linolenic acid GLA: 18:3n-6 , which is metabolized from linoleic acid LA: 18:2n-6 , is known for its benefi cial effect such as improvement of lipid profi les 3 or alleviation of premenstrual syndrome PMS 4 . And GLA is also one of the most popular treatments available for dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Sayantani et al was the only study showing that dietary GLA feeding resulted in significant decrease in serum TG and very low density lipoprotein (VLDL) cholesterol in addition to the significant increase in HDL-C [ 32 ].…”
Section: Discussionmentioning
confidence: 99%